1984
DOI: 10.1149/1.2115629
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Junction Between Two Solid Electrolytes for the Potentiometric Measurement of Gaseous Oxides

Abstract: The contact between two solid electrolytes such as a stabilized zirconia and potassium sulfate can be used to measure the activity of volatile oxides, SO2 or SO~ for instance. On this basis, a new type of sensor has been designed which produces stable voltages logarithmically dependent on the concentration of the gas to be measured. This principle was extended to the measurement of other gaseous oxides, namely carbon oxides, using K2CO~ as the electrolyte. The range of these sensors covers a few parts per mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The term in the parenthesis of Eq. 12 is the standard Gibbs free-energy change (AG') of the reaction Li2SO4 + Li3Mg,Zr03 = Li3÷32Mg,Zr03 + 503 [13] The first term of Eq. 12 is thus constant (E,), allowing us to express EMF as…”
Section: Resultsmentioning
confidence: 99%
“…The term in the parenthesis of Eq. 12 is the standard Gibbs free-energy change (AG') of the reaction Li2SO4 + Li3Mg,Zr03 = Li3÷32Mg,Zr03 + 503 [13] The first term of Eq. 12 is thus constant (E,), allowing us to express EMF as…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained by Jorgensen (7, 8, I0), for instance, seem to confirm this effect, although other authors (14,15) did not find any influence of the external electric field on the oxidation kinetics. The reason for this probably lies in the difficulties both in measuring the potential difference at the growing oxide interfaces (16,17), and in…”
Section: Resultsmentioning
confidence: 99%
“…Bourhis and St. John (7) have shown that the catastrophic corrosion of superalloys containing Mo is due to fluxing by M003, which is formed at the scale-metal interface. Studies in this laboratory (3,8) have shown that all the Na~SO4 was converted to Na~CrO, much before the onset of catastrophic corrosion for superalloys containing Mo, and the onset of catastrophic corrosion was marked by the conversion of Na~CrO4 to Na~MoO4. The catastrophic corrosion was associated with the formation of a Na2MoO4--M003 melt.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali-metal sulfates (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) have been extensively investigated as solid electrolytes for a sulfur dioxide gas detector. However, phase transformation of the sulfates occurs, resulting in gas permeation through the microcracks in the electrolyte.…”
mentioning
confidence: 99%